2017
DOI: 10.18203/2320-6012.ijrms20171539
|View full text |Cite
|
Sign up to set email alerts
|

A study of the clinical profile of 50 patients of COPD with correlation between clinical, radiological and spirometric evaluation

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common, preventable and treatable disease that is characterised by persistent respiratory symptoms and airflow limitation that is due to airway and/ or alveolar abnormalities usually caused by significant exposure to noxious particles or gases. Tobacco smoking, occupational exposure to organic and inorganic dusts, chemical agents and fumes and biomass cooking are the risk factors for COPD. Chronic dyspnoea, cough, sputum production, wheezing and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Similar findings were reported by Gupta et al (2015) in Rajasthan (8) and by R Ramakrishna et al in Guntur. (2) The current study also shows that COPD patients with low FEV1/FVC % values have more ECG changes in comparison to those with higher FEV1/FVC % values. And as the severity of airflow obstruction increases (fall in FEV1), ECG changes also becomes more common.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Similar findings were reported by Gupta et al (2015) in Rajasthan (8) and by R Ramakrishna et al in Guntur. (2) The current study also shows that COPD patients with low FEV1/FVC % values have more ECG changes in comparison to those with higher FEV1/FVC % values. And as the severity of airflow obstruction increases (fall in FEV1), ECG changes also becomes more common.…”
Section: Discussionsupporting
confidence: 69%
“…On the contrary a study by Kamdar DJ et al (2017) in Gujarat (2) reported that P-pulmonale was observed only in 20% of the COPD patients. A study by Chappell AG (10) reports that 70% of cases showed right axis deviation of QRS complex (Beyond +90 degrees).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On Spirometry, 38.33% of patients had Moderate obstruction and severe obstruction in 30% of patients. 13,14…”
Section: Resultsmentioning
confidence: 99%